Data-Driven Real Estate Pricing: Leveraging Extra Trees Regressor for Improved Market Predictability - Bathula Revathi, CH. Pavani, U. Chandana, K. Harish, B. Srikanth (Journal of Computational Analysis and Applications (JoCAAA), 2025)
Zestimate plays a significant role in shaping real estate market decisions, with Zillow estimatingproperty values for more than 104 million homes in the United States and influencing nearly 60% ofbuyers and sellers. Despite its widespread adoption, Zestimate has faced criticism due to valuation inaccuracies, reporting median errors